Insecticidal activity of individual and mixed monoterpenoids of geranium essential oil against pediculus humanus capitis (Phthiraptera: Pediculidae) - Gallardo, Anabella Beatriz (2012)
The major components of geranium (Geranium maculatum L.) oil and their mixtures were tested against female Pediculus humanus capitis De Geer (Phthiraptera: Pediculidae). Chemical analysis by gas chromatography coupled to mass spectrometry revealed four major constituents: citronellol (38%), geraniol (16%), citronellyl formate (10.4%), and linalool (6.45%) (concentration expressed as percentage of total). Topical application demonstrated that the most potent component was citronellol and geraniol, with LD 50 values 9.7 and 12.7 μg/insect, respectively. Linalool and Citronellyl formate were less toxic with LD 50 values 24.7 and 38.5 μg/insect, respectively. Toxicity of these four major constituents in the same proportion as the natural oil, was greater than whole oil and each individual component. Removal of any four constituents produced a decreased in effectiveness. The absence of citronellol caused the greatest decrease in toxicity (DL 50 from 2.2 to 10.9 μg/insect), leading us to conclude that this constituent is the major contributor to oil toxicity. The knowledge of the role of each constituent in the toxicity of the whole oil gives the possibility to create artificial blends of different constituents for the development of more effective control agents.